Orientation competition growth and mechanism of SrTiO3 film on CeO2 layer. (December 2021) - Ye, Jiachao; Mou, Shaojing; Zhu, Rongji; Liu, Linfei; Li, Yijie
Abstract: A series of SrTiO3 films were deposited on CeO2 layer by pulsed laser deposition at substrate temperature in the range of 300 °C–700 °C. It was found that the (110)-oriented and (200)-oriented SrTiO3 grains coexisted on the CeO2 layer. Although the (110)-oriented grains dominated during the deposition, the dominance was weakened with increasing substrate temperature. The competition mechanism of SrTiO3 grains along different orientations was explained in view of the diffusion energy and the evolution of dislocation density. The dependence of the film stoichiometry on the substrate temperature and the effects of residual contaminants in the chamber were also studied by X-ray photoelectron spectroscopy. Highlights: (110)-oriented and (200)-oriented SrTiO3 grains coexist on CeO2 layer. The growth advantage of (110)-oriented grain is determined by diffusion energy. The dominance of (110)-oriented grain weakens at a higher substrate temperature. The weakening can be explained by the evolution of dislocation densitny.